2010
DOI: 10.1038/clpt.2010.62
|View full text |Cite
|
Sign up to set email alerts
|

Donor P-gp Polymorphisms Strongly Influence Renal Function and Graft Loss in a Cohort of Renal Transplant Recipients on Cyclosporine Therapy in a Long-Term Follow-Up

Abstract: Cyclosporin A (CsA) is a substrate for cytochrome P450 3A and the efflux transporter P-glycoprotein (P-gp; ABCB1), both abundantly expressed in the kidney. In a long-term follow-up of a cohort of patients who had received kidney transplants between the years 1990 and 2005, we retrospectively investigated the effect of CYP3A4, CYP3A5, and ABCB1 polymorphisms in kidney graft donors on recipients' renal function and risk of subsequent graft loss. DNA samples from 227 donors and clinical data from the 259 respecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
49
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(55 citation statements)
references
References 26 publications
5
49
1
Order By: Relevance
“…These studies have shown evidence for an association between donor TT genotype and adverse outcome, 17,18,21 rather than CC genotype as seen in the current study. In the first study of 99 patients, donor TT genotype correlated with the development of acute cyclosporine nephrotoxicity, 17 defined on clinical grounds after a retrospective records review.…”
Section: Discussionsupporting
confidence: 54%
See 3 more Smart Citations
“…These studies have shown evidence for an association between donor TT genotype and adverse outcome, 17,18,21 rather than CC genotype as seen in the current study. In the first study of 99 patients, donor TT genotype correlated with the development of acute cyclosporine nephrotoxicity, 17 defined on clinical grounds after a retrospective records review.…”
Section: Discussionsupporting
confidence: 54%
“…In the first study of 99 patients, donor TT genotype correlated with the development of acute cyclosporine nephrotoxicity, 17 defined on clinical grounds after a retrospective records review. A second study of 259 prevalent transplant recipients with functioning grafts at 12 months post-transplantation suggested that the presence of the homozygous form of a "variant" donor haplotype (which included the TT genotype at ABCB1 C3435T) was associated with increased graft failure rates during a followup of 6 years, 18 with failures due to "clearly identifiable causes" excluded from analysis. Finally, a histology-based study of the same ABCB1 SNP showed an association between donor TT genotype and the development of interstitial fibrosis and tubular atrophy on protocol biopsy specimens taken up to 3 years post-transplantation in patients treated with tacrolimus.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the kidney transplant setting there have been relatively few studies looking at the role of polymorphisms in graft donors and their conclusions remains unclear. Woillard et al [34] reported that the presence of ABCB1 polymorphisms in donors influenced long-term graft outcome of renal transplant patients. Nevertheless, Hauser et al [35] reported that in adult renal transplant recipients the incidence of cyclosporine nephrotoxicity was significantly higher when the donor rather than the recipient, had the ABCB1 3435TT genotype.…”
Section: The Effect Of Donor Genetic Polymorphisms On the Transplant mentioning
confidence: 99%